Thermal Behavior of Water-Electrolyte Mixtures: Structural and Ionic Influences - Kambarova, Galiya; Nazarbek, Ulzhalgas; Raiymbekov, Yerkebulan (Engineering, Technology & Applied Science Research, 2025)
This study investigates the thermal properties of water-electrolyte mixtures, specifically focusing on binary and ternary electrolyte solutions over a concentration range of 0.01 mol%–23.5 mol% at two constant temperatures (20°C and 40°C). The results indicate that the specific Heat Capacity (Cp) and Thermal Conductivity (λ) exhibit polynomial dependencies on the ionic radius and charge density. As the ionic radius increases from 0.72 Å (Co²⁺) to 1.65 Å (Cs⁺), Cp decreases by up to 12%. As the charge density increases from 0.0468 C/Å² (Cs⁺) to 0.4921 C/Å² (Co²⁺), Cp increases by up to 15%, while λ decreases by 8%-20% with an increasing charge density, confirming the influence of hydration. These results provide a quantitative framework for electrolyte-based thermal applications in energy storage, water treatment, and thermodynamic modeling.